Characteristics of Jelly Candy made from Soybean Milk and Addition of Eggshell Powder - Novelina, Novelina; Anggraini, Tuty; Putri, Lailita Nurrahmi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
Jelly is a soft textured candy that is processed by the addition of hydrocolloid components such as agar, gum, pectin, starch, carrageenan, gelatin and others that are used for texture modification to produce a chewy product. The purpose of this study was to determine the appropriate addition of chicken eggshell powder to soy milk jelly candy characteristics and to determine panelist acceptance. This study used a Completely Randomized Design (CRD) consisting of 5 treatments: the addition of chicken eggshell powder concentrations namely 0%, 0.2%, 0.4%, 0.6% and 0.8% of the total ingredients for the manufacture of jelly candy with 3 replications. Observations on soy milk jelly candies are pH, water content, ash content, reducing sugars, sucrose, calcium, protein, water activity (aw), gel strength, total plate count, and organoleptic tests. The results showed that the difference in the addition of chicken eggshell powder concentration to soymilk jelly candy significantly affected pH, water content, ash content, reducing sugar content, sucrose, calcium, and gel strength, but did not significantly affect protein and water activity (aw). best results are soy milk jelly candy added with 0.8% chicken eggshells powder, with the highest calcium content of 0.51%, 15.46% moisture content, 1.32% ash content, 50.55% sucrose content, content reducing sugar 5.58%, protein content 2.93%, total plate rate 3.1 x 103 CFU / g, and gel strength 269.17 N / cm2.